The role of MACF1 in nervous system development and maintenance - Moffat, Jeffrey J. (Semin Cell Dev Biol, 2017)
Microtubule-actin crosslinking factor 1 (MACF1), also known as actin crosslinking factor 7 (ACF7), is essential for proper modulation of actin and microtubule cytoskeletal networks. Most MACF1 isoforms are expressed broadly in the body, but some are exclusively found in the nervous system. Consequentially, MACF1 is integrally involved in multiple neural processes during development and in adulthood, including neurite outgrowth and neuronal migration. Furthermore, MACF1 participates in several signaling pathways, including the Wnt/β-catenin and GSK-3 signaling pathways, which regulate key cellular processes, such as proliferation and cell migration. Genetic mutation or dysregulation of the MACF1 gene has been associated with neurodevelopmental and neurodegenerative diseases, specifically schizophrenia and Parkinson’s disease. MACF1 may also play a part in neuromuscular disorders and have a neuroprotective role in the optic nerve. In this review, the authors seek to synthesize recent findings relating to the roles of MACF1 within the nervous system and explore potential novel functions of MACF1 not yet examined.